A invenção do mito nacionalista no Brasil Contemporâneo: uma cidadania forjada? (2015-2020): The invention of the nationalism myth in Contemporary Brazil: a forged citizenship? (2015-2020) (Revista de História da UEG (REVHIST), 2021)
The purpose of this paper is to discuss how the problem of nationalism has been shaped in the last three years in Brazil. It is no coincidence that the idea of the nation, its uses and abuses, has become the motto and the north of the current government's electoral campaign, and, consequently, a fundamental rhetorical basis for its legitimation process. We do not seek to argue about the already canonical conceptual definitions of nationalism and its aspects, but to think about it from the category of political myth. The hypothesis is that there is a possible correlation between the invention of this nationalist myth and the creation of an ideal of citizenship.Keywords: Nationalism. Myth. Citizenship.